Nanostructured Hybrid Metal Mesh as Transparent Conducting Electrodes: Selection Criteria Verification in Perovskite Solar Cells - John Mohanraj; Chetan R. Singh; Tanaji P. Gujar; C. David Heinrich; Mukundan Thelakkat (Nanomaterials, 2021)
Nanostructured metal mesh structures demonstrating excellent conductivity and high transparency are one of the promising transparent conducting electrode (TCE) alternatives for indium tin oxide (ITO). Often, these metal nanostructures are to be employed as hybrids along with a conducting filler layer to collect charge carriers from the network voids and to minimize current and voltage losses. The influence of filler layers on dictating the extent of such ohmic loss is complex. Here, we used a general numerical model to correlate the sheet resistance of the filler, lateral charge transport distance in network voids, metal mesh line width and ohmic losses in optoelectronic devices. To verify this correlation, we prepared gold or copper network electrodes with different line widths and different filler layers, and applied them as TCEs in perovskite solar cells. We show that the photovoltaic parameters scale with the hybrid metal network TCE properties and an Au-network or Cu-network with aluminum-doped zinc oxide (AZO) filler can replace ITO very well, validating our theoretical predictions. Thus, the proposed model could be employed to select an appropriate filler layer for a specific metal mesh electrode geometry and dimensions to overcome the possible ohmic losses in optoelectronic devices.